INDUSTRY 4.0: MANAGERIAL ROLES AND CHALLENGES - Ismail Sheik; Pratik Kumar Singh (International Journal of Innovations in Engineering Research and Technology, 2021)
The Fourth Industrial Revolution is abruptly changing the business processes and the way of doing business in the world. Competition is going to be fierce and there will not be any geographical advantage to local manufacturing units as the world is going to connect with IoT. With all these challenges, managerial roles are going to change. Managers have to play a pivotal role in industry 4.0 as there will be the challenge to convert the present workforce in to smart workers whilst adapting to technological advancements that is already creeping in. Managers not only need to prepare themselves for the challenge but also to train their workforce to deal with the technological revolution. This paper discusses the managerial challenges within industry 4.0.